Pengaruh Digital Marketing Dan Inovasi Produk Tehadap Keberhasilan Kewirausahaan (Studi Kasus Umkm Bungo Tanjung Desa Rambutan Masam Kecamatan Muara Tembesi) - Mira Syilvia Putri; Zilawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Entrepreneurial success is a condition where a person is able to achieve success in business with entrepreneurship in an entrepreneur The development of small and medium enterprises is expected to be better because of the increasing openness of business opportunities and the consolidation among smes in overcoming limited access to capital especially in the current era, namely the era of gen Z and the influence of technology, various challenges are faced by smes. Therefore, smes must have a high entrepreneurial spirit in order to compete with other smes. smes struggle to survive with various challenges Based on the theory and understanding of digital marketing, it can be formulated in synthesis that digital marketing is a marketing strategy and product or brand promotion in a business using digital media.